A time domain prediction method for the vortex-induced vibrations of a flexible riser. (May 2018) - Zhang, Mengmeng; Fu, Shixiao; Song, Leijian; Tang, Xiaoying; He, Yue
Abstract: In this paper, a time domain prediction method from experimental data is proposed for vortex-induced vibration (VIV) of flexible risers. The nonlinear factors, couplings among axial tension, VIV response in cross flow (CF) direction and the hydrodynamic force, have been taken into account in this method, with a simplified tension variation model and empirical hydrodynamic force model. The hydrodynamic force, including the excitation force in the excitation region and the damping force in the damping region are the function of excitation coefficients, non-dimensional VIV amplitude and frequency based on vibration experiment data. Iterations are performed to achieve balances between the hydrodynamic forces and the VIV responses of a riser. Moreover, a new added mass coefficient of 2.0 from model tests of flexible pipes is applied, where the predicted VIV response frequencies reveal higher accuracy. Comparison between the predicted results and the experimental results under uniform flow of 2.8 m/s and shear flow of 2.0 m/s are conducted, which verifies the feasibility and reliability of the proposed method. In addition, by comparing the prediction results with and without coupling between axial tension and VIV responses, it is found that this coupling effect is of importance to VIV prediction and can improve VIV prediction accuracy, especially under the case of high flow velocity and high vibration mode. Highlights: An empirical time domain prediction method is proposed for vortex-induced vibration of flexible risers. The couplings among axial tension, CF VIV and hydrodynamic force are taken into account. A newly added mass coefficient of 2.0 is applied. The coupling effect is important to VIV prediction and can improve prediction accuracy, especially under high flow velocities.